Chlorophyll a data from the Boknis Eck time series station 2015 to 2021 - Hermann W Bange; Kerstin Nachtigall; Levka Hansen; Helmke Hepach; Kastriot Qelaj; Frank Malien (PANGAEA, 2025)
The dataset was acquired at the time-series station Boknis Eck (54.5°N and 10.0°E) at six standard depths (1, 5, 10, 15, 20, 25 m). The dataset contains data for Chlorophyll a (sampled with a rosette sampler, measured using a fluorometer until 2019 and using high performance liquid chromatography from 2019). The data are from 2015 to 2021.